2011
DOI: 10.1002/cctc.201100064
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase‐Like Activity of Cupric Oxide Nanoparticle

Abstract: Almost all processes in a biological cell need enzymes to occur at significant rates. Since enzymes are selective for their substrates and speed up only a few reactions from among many possibilities, the set of enzymes made in a cell determines which metabolic pathways occur in that cell. Besides their fundamental importance, natural enzymes also have significant practical applications in medicine, chemical industry, food processing, and agriculture due to their excellent properties, such as high substrate spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
101
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(105 citation statements)
references
References 50 publications
2
101
0
2
Order By: Relevance
“…In general, nanozymes require a higher peroxide concentration than HRP to reach the maximum activity. 34,35,38 Interestingly, our core-shell NPs escape this trend.…”
Section: Reactivity Of Core-shell Nps As Artificial Enzymesmentioning
confidence: 76%
See 3 more Smart Citations
“…In general, nanozymes require a higher peroxide concentration than HRP to reach the maximum activity. 34,35,38 Interestingly, our core-shell NPs escape this trend.…”
Section: Reactivity Of Core-shell Nps As Artificial Enzymesmentioning
confidence: 76%
“…As a matter of fact, if H 2 O 2 is tested as a substrate, by changing its concentration in the presence of 0.2 mM TMB the TC1 K M app value increases by about 20 times and its calculated value (6.29 mM) is higher than that measured for HRP, 34 however order of magnitude smaller than other oxides (CuO 85.6 mM, Fe 3 O 4 154 mM, see Table 1) 34,35 and comparable with other highly efficient mimics (graphene oxide 3.99 mM, FeS 7.2 mM). 36,38 Surprisingly, also TC3 shows an increase of the K M app (1.39 mM), but quite modest, smaller than the natural enzyme.…”
Section: Reactivity Of Core-shell Nps As Artificial Enzymesmentioning
confidence: 88%
See 2 more Smart Citations
“…Being inspired by the application of peroxidase, various nanomimetics, such as Fe 3 O 4 nanoparticles (Zhang et al 2008(Zhang et al , 2009), gold nanoparticles (Han et al 2008), iron oxide-based nanoparticles (Zelmanov and Semiat 2008), and c-FeOOH nanosheets (Peng et al 2011), have been used as catalysts for the catalytic oxidation of phenol. In the previous study, we have found that cupric oxide nanoparticle is a highly effective catalyst to peroxidase substrates, and the binding affinity for the substrate 3,3',5,5'-tetramethylbenzidine (TMB) is higher than that of HRP and other peroxidase nanomimics (Chen et al 2011). Based on this finding, we studied in this work the potential application of cupric oxide nanoparticles in phenol removal.…”
Section: Introductionmentioning
confidence: 92%